جماليات الموسيقى والإيقاع في شعر الأسود بن يعفر النهشلي - عيسى حكمت; إبراهيم محمد (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يتناول البحث دراسة الموسيقى الشعرية عند الأسود بن يعفر النهشلي, عبر التحليل الصوتي لبعض قصائده, واستخلاص السمات الموسيقية. من إيقاع ووزن, وما تتضمنّه البحور الشعرية من تفعيلات, و كشف الخفايا النفسية, والمضامين الإبداعية,والدلالات الإيحائية العميقة, ممّا أ كسبها بعدا جماليا موحيا. بالإضافة إلى دراسة الحروف المنتقاة, والألفاظ المختارة, والتراكيب المناسبة للغرض الشعري في نسيج متآلف, خلال البحور الشعرية الطويلة, من جهة, والقصيرة من جهة أخرى, مساهمة في خلق الموسيقى المتناغمة على وفق دراسة إحصائية للحروف, وتكرارها و أنواعها.مهموسة أو مجهورة, شديدة أو رخوة لينّة, كما عمدنا إلى وضع جداول تبيّن تكرار الحروف من جهة, واستخراج النسب من أنموذج شعريِّ لإحدى قصائده بدراسة متعمقّة من جهة أخرى. أمّا القافية فحظيت بدراسة خاصّة, أشرنا فيها إلى آراء القدامى والمحدثين. واختتمنا البحث بدراسة موجزة للرويُّ ضمن إحصائّية, للكشف عن الأغراض الشعرية,ومعانيها, ودلالاتها التّي أفصحت عنها القوافي الشعريَّة عند الأسود بن يعفر. The research deals with the study of poetic harmony in Al-Asswad Ben Yaafar, through the vocal analysis of some of his poems, and extracting the musical aspects, of meter and cadence, the revelation of mind secrets, the creative contents and the deep suggestive connotations which provided them with an inspiring aesthetic dimension. In addition, studying the selected letters and the chosen articulations, the structures suitable for the poetic purpose in a harmonious texture, throughout the long poetic meters, on one side, and the short ones on the other side, contributing in the creation of harmonious music based on a statistical study of letters, their frequency and kind, audible or murmur, strong or lenient, tabulating repetition of letters on one hand, and extracting the rates from a poetic sample of one of his poems in a profound study on the other hand. The narrator has also acquired great outstanding throughout the prosodic study within a statistic uncovering the poetic purposes, their meanings, connotations of which the poetic rhymes have divulged in Al-Asswad Ben Yaafar’s.